Propranolol for treatment of infantile hemangiomas - Juliana Nakano de Melo; Anita Rotter; Maria Cecília Rivitti-Machado; Zilda Najjar Prado de Oliveira (Sociedade Brasileira de Dermatologia, 2013)
Infantile hemangioma is the most common vascular tumor in early childhood. Propranolol has been successfully used recently in a limited number of children with Infantile hemangioma. We present 6 cases of Infantile hemangioma, at a single dermatological center, which responded to oral propranolol with good results.